Genetic variants of epidermal growth factor receptor (EGFR) and their association with colorectal cancer risk in North Indian population - Uroog, Laraib; Bhat, Zafar Iqbal; Imtiyaz, Khalid; Zeya, Bushra; Wani, Rauf Ahmad; Rizvi, M. Moshahid A. (Gene reports, 2020)
Most of the cancer types contain single nucleotide polymorphisms (SNPs) that are associated with a large number of genes. These SNPs are located in gene promoters, exons, introns as well as untranslated regions (UTRs) and influence gene expression by diverse mechanisms. These mechanisms depend on the role of the genetic elements in which the individual SNPs are located. We aimed to examine the possible association of EGFR rs11543848 and rs2227984 gene polymorphism and colorectal cancer in North Indian population. Subjects and methods: Peripheral blood samples were collected and genomic DNA was extracted by phenol chloroform Isoamyl method. Presence or absence of polymorphism was analyzed by PCR-RFLP method and direct sequencing. The frequency of G allele at rs11543848 was found to be higher in cases than in controls. This suggests that individual with either homozygous G or heterozygous G allele (GA + GG) at rs11543848 SNP site were at a higher risk for developing colorectal cancer (P = 0.0358) while at rs2227984, variant genotype AA (19.3%) and TA (51.7%) were more frequent in patients than in healthy controls (AA-13%, TA-46.7%) signifying the association of this SNP with colorectal cancer patients of North India. Excellent correlation of rs11543848 was found with the clinicopathological factors and haplotypes suggested that rs11543848 might be a good prognostic factor for genetic susceptibility to CRC in North Indian population. •EGFR SNPs rs11543848 and rs2227984 are associated with colorectal cancer.•In rs11543848 GA and GA + AA genotypes displayed significant association with all the clinicopathological characteristics.•The two haplotype frequencies were not found in strong LD but the genotypes seem to be associated with good prognosis.